Medicolegal aspects of medical malpractice claims following aesthetic interventions in Cairo, Egypt - Ghada Abdelwahed Rawash; Neveen Adel Ibrahim; Islam Mostafa Farrag; Somaya Youssef Mostafa (Egyptian Journal of Forensic Sciences)
Abstract Background Medical malpractice presents a significant challenge to the healthcare system in Egypt and other countries, inflicting both physical and psychological harm on patients. Furthermore, it imposes a financial burden on both patients and physicians. This study aimed to analyze the medicolegal aspects of malpractice claims associated with aesthetic interventions. The study also aims to establish explicit criteria for identifying and differentiating positive cases from negative ones. This study is a retrospective descriptive observational analysis of medical malpractice claims related to aesthetic interventions. The data was obtained from the records of the Cairo Medicolegal Area between 2016 and 2020, encompassing a total of 98 cases in the study. Results The majority of cases were females (89.8%). The age group most significantly affected was between 26 to 35 years old. Plastic surgery accounted for the highest percentage (51%) of alleged cases among medical specialties. Consultants were the most frequently accused physicians (32.7%). Liposuction was the most frequent procedure (31.6%). Most of the malpractices occurred in private hospitals (45.9%). The outcome indicated that permanent infirmity accounted for 10.2%, while mortality constituted 3.1%. Conclusions The current study demonstrated that women constitute the predominant demographic in the examined malpractice cases, with plastic surgery being the most common area for alleged claims. The main complaints include disfigurement, dissatisfaction with results, and burn injuries. Aesthetic malpractice is more frequent in private hospitals than in general hospitals, frequently necessitating further treatment due to complications.